Existence of the solution of a Schrödinger type homogeneous model in periodic Sobolev spaces - Candia Estrada , Víctor (2022)
In this article we prove that the Cauchy problem associated to a Schrödinger type homogeneous model in periodic Sobolev spaces is well posed. We do this in an intuitive way using Fourier theory and in a fine version using Groups theory, inspired by works Iorio [3], Santiago and Rojas [10] and [11]. Finally, we study the relationship between initial data and differentiability of the solution.